Investigating University EFL Teachers’ Feedback Literacy and Practices in the Kurdistan Region of Iraq (Raparin Journal of Humanities (RJH), 2026)
With the changes and development of educational systems worldwide, feedback has received scholarly attention. Student learning depends on effective feedback, but giving appropriate feedback has proved to be a challenge to both teachers and students. This study investigates teachers’ feedback literacy and practices at universities in the Kurdistan Region of Iraq from the perspectives of the students. It also aims to explore the types of feedback that teachers provide to enhance students’ learning outcomes and motivate them through learning from the feedback. To achieve this aim, a semi-structured questionnaire was used, including both close-ended questions and open-ended questions. The participants were 211 third-year and fourth-year students of English department at Soran university. The results indicated that students had a positive attitude towards providing different types of feedback. The participants also preferred receiving individual feedback from teachers rather than general feedback in front of their classmates. The results also showed that students perceived significant inconsistency in the feedback they receive from different teachers and emphasize the importance of more standardized and coordinated approaches to ensure clarity, fairness, and effectiveness. Moreover, the results showed that feedback in front of classmates, general feedback, self-consciousness, teachers' bias, and limited time are the most common challenges that students face while receiving feedback.